2006
DOI: 10.1177/0165025406071489
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being in mid to late life: The role of generativity development and parent–child relationships across the lifespan

Abstract: This study examined the association between generativity and psychological well-being for a subsample of 1882 mid- to late-life parents using the MIDUS data set. Guided by Erikson's theory of psychosocial development, we tested a structural model of psychological well-being that also included direct and indirect effects (via generativity) of remembered pre-adult relationships with parents and current parental experiences with offspring on well-being. Respondents who recalled positive, trusting relationships wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(143 citation statements)
references
References 43 publications
8
129
2
4
Order By: Relevance
“…Low relationship quality between parents and adult children (e.g., An and Cooney 2006;Koropeckyj-Cox 2002) or burdens associated with providing care to kin (e.g., Call et al 1999;Sherwood et al 2005), on the other hand, have been shown to result in health deterioration, especially if psychological well-being is considered. The individual's trust in the family network as a potential source of support and the emotional stability of family relations appear to be particularly important here.…”
Section: Intergenerational Family Relations and Healthmentioning
confidence: 99%
“…Low relationship quality between parents and adult children (e.g., An and Cooney 2006;Koropeckyj-Cox 2002) or burdens associated with providing care to kin (e.g., Call et al 1999;Sherwood et al 2005), on the other hand, have been shown to result in health deterioration, especially if psychological well-being is considered. The individual's trust in the family network as a potential source of support and the emotional stability of family relations appear to be particularly important here.…”
Section: Intergenerational Family Relations and Healthmentioning
confidence: 99%
“…O BEP tem se correlacionado positivamente com autoestima e moral (Ryff, 1989), satisfação de vida e afetos positivos (Ryff, 1989), coping (Holland & Holahan, 2003), geratividade (An & Cooney, 2006;Queroz & Neri, 2005), memórias integrativas e intrínsecas (Bauer & McAdams, 2004a;Bauer et al, 2005), generosidade (Konow & Earley, 2008), habilidades sociais (Segrin & Taylor, 2007), inteligência emocional (Queroz & Neri, 2005), valores intrínsecos (Sheldon, 2005), resiliência (Ryff, Keyes, Hughes, 2003) e metas intrínsecas de crescimento (Bauer & McAdams, 2004b).…”
Section: Correlatos Psicossociais E Sociodemográficos Do Bepunclassified
“…Accordingly, identity commitment is essential for one's well-being (e.g., Berzonsky, 2003;Fadjukoff & Pulkkinen, 2006;Meeus, Iedema, Helsen, &Vollebergh, 1999;Sneed, Whitbourne, Schwartz, & Huang, 2012;Vleioras & Bosma, 2005). In addition, generativity-the adult's concern for and commitment to guiding and caring for the next generation-has been identified as a key developmental task and precondition for psychological well-being, particularly in middle age (An & Cooney, 2006;Erikson, 1950Erikson, , 1959. Marcia (2002) depicted that identity achievement in late adolescence would lead to generativity in middle age, whereas identity diffusion would more likely be succeeded by a sense of personal and interpersonal stagnation when one feels isolated from others and finds difficulties in giving and receiving care.…”
Section: Introductionmentioning
confidence: 99%
“…Generativity has been found to be associated with an authoritative, child-centered, parenting style that produces positive outcomes (Peterson et al, 1997). Parenting behavior, characterized by selfless care and concern, is an important way for adults to achieve generativity and personal well-being (An & Cooney, 2006).…”
Section: Introductionmentioning
confidence: 99%